Uniform lithium electrodeposition for stable lithium-metal batteries - He, Xin; Yang, Yang; Cristian, Marian Stan; Wang, Jun; Hou, Xu ; 0000-0003-0398-2006; Yan, Bo; Li, Jinke; Zhang, Tong; Paillard, Elie; Swietoslawski, Michal; Kostecki, Robert; Winter, Martin; et al. (Nano Energy, 2020)
A lithium-metal composite is proposed, which includes a carbon-nitrogen modified stainless steel mesh (CNSSM) favoring homogeneous lithium-metal nucleation and growth of fresh and dense lithium deposits when employed as anode for lithium-metal batteries. This novel approach is able to overcome the usual drawbacks linked to the preexisting passivation layer at the surface of lithium. Instead, a favorable interphase with low resistivity is formed with the electrolyte, and the CNSSM modified lithium-metal composite (CNSSM-Li) results in low-voltage hysteresis (±24 mV) and allows stable and dendrite-free lithium electrodeposition. The performance of lithium-metal batteries demonstrates the outstanding capabilities of the novel CNSSM-Li electrode in promoting cell energy density and cycling stability. In addition, advanced X-ray nano-tomography is employed to characterize the composition and morphology changes of this electrode upon plating.
Publisher Copyright: © 2019 Elsevier Ltd
Keywords: Dendrite; Lithium-metal batteries; X-ray nano-tomography